160 Case Report: Primary Effusion Lymphoma in an 88-Year-Old Man. (11th January 2018) - Li, Yilan; Henn, Patrick; Zhang, Yingtao; Sands, Amy; Zhang, Nan
Abstract: Primary effusion lymphoma is a rare large B-cell lymphoma most commonly arising in patients with HIV or severe immunodeficiency. The patients usually present with pleural or pericardial effusion without lymphadenopathy or organomegaly. Here we report a case of an 88-year-old gentleman with a history of severe aortic stenosis, atrial fibrillation, and congestive heart failure who developed shortness of breath, jaundice, hyperbilirubinemia, and anemia. He was found to have bilateral pleural effusion (left > right) on CT. Thoracentesis showed discohesive abnormal large cells with high N:C ratio and prominent nucleoli in the background of many neutrophils. The abnormal large cells are positive for human herpesvirus 8, CD30, CD43, EMA, and CD45 (weak), and negative for CD138, CD20, CD79a, CD3, CD5, CD15, CD56, CD68, MPO, and all other markers tested. A diagnosis of primary effusion lymphoma was rendered, and the patient expired one week after the diagnosis. Reviewing the medical record revealed asymmetrical moderate to large amount of bilateral pleural effusion present at least two months on CT. However, the etiology of the pleural effusion was thought to be related to the cardiovascular diseases. This primary effusion lymphoma is unique in several aspects including the occurrence in a nonimmune-suppressed patient, negative CD138 expression, and multiple confounding factors that may have contributed to the delay of diagnosis.